3D Assembly Group Analysis for Cognitive Automation. (4th March 2012) - Brecher, Christian; Breitbach, Thomas; Müller, Simon; Mayer, Marcel Ph.; Odenthal, Barbara; Schlick, Christopher M.; Herfs, Werner
Abstract : A concept that allows the cognitive automation of robotic assembly processes is introduced. An assembly cell comprised of two robots was designed to verify the concept. For the purpose of validation a customer-defined part group consisting of Hubelino bricks is assembled. One of the key aspects for this process is the verification of the assembly group. Hence a software component was designed that utilizes the Microsoft Kinect to perceive both depth and color data in the assembly area. This information is used to determine the current state of the assembly group and is compared to a CAD model for validation purposes. In order to efficiently resolve erroneous situations, the results are interactively accessible to a human expert. The implications for an industrial application are demonstrated by transferring the developed concepts to an assembly scenario for switch-cabinet systems.